Analisis Hukum Kualitas Alat Bukti Tindak Pidana Pencurian: (Studi Putusan Nomor 81/PID.B/2020/PN TOB) - Anshar Anshar; Edhy Muhammad; Syawal Abdulajid (CV Rewang Rencang, 2025)
This research examines the Quality of Evidence for the Crime of Theft in Decision Number 81/PID.B/2020/PN Tob.This research uses doctrinal legal research methods with statutory and conceptual approaches. The results showed that Decision Number 81/PID.B/2020/PN Tob which acquitted the defendant Hendri Novita alias Hendrik from the charge of theft showed that the quality of evidence submitted by the Public Prosecutor (JPU) did not meet the standard of proof as stipulated in Article 183 in this case, the testimony of witnesses could not prove that the defendant directly took or placed ore stones belonging to PT NHM into the car he was driving. although the element of the subject of law (the element of